Sistem Informasi Kepegawaian Berbasis Web Studi Kasus PT. Hara Sentosa Mandiri - Pamungkas, Panji Putra; Danny, Muhtajuddin; Muhidin, Asep (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Human Resource Information System (HRIS) is a very important system in an organization or institution, which aims to manage employee data, employee attendance, employee salaries, and so on. However, at present there are still many organizations or institutions that still use traditional systems. PT. Hara Mandiri Sentosa is one of the private companies that has not adopted an integrated human resource information system, such as using employee data with books, attendance filled in in writing by employees, and salary calculations that are summarized through the attendance so that they are prone to errors in the process. This research aims to build a web-based human resource information system using the waterfall method. The results of this study indicate that the system that was built can overcome the risk of errors in the process. This system is able to make the processing of human resource data more efficient and data security guaranteed.